2017
DOI: 10.1049/mnl.2016.0666
|View full text |Cite
|
Sign up to set email alerts
|

Optical and antibacterial properties of synthesised silver nanoparticles

Abstract: In the present study, tri-sodium citrate has been used as both the reducing agent and stabiliser for the synthesis of silver nanoparticles (AgNPs). Sodium borohydride (NaBH 4) was used in various concentrations. The absorbance of AgNP solution was measured after the addition of NaBH 4. The samples were characterised by ultraviolet-visible spectroscopy after 5, 10, 15, 25, 60 and 120 min of synthesis to investigate the stability of AgNPs for different concentrations of NaBH 4. Transmission electron microscopy r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…[9] . Previously, the antibacterial action of Ag-based NPs based on dissolved Ag (I) had been reported [9,10,19]. In this work, our results showed that compared to AgNP, Ag (I)-supporting SiO 2 has a significant increase in antibacterial activity.…”
Section: Agnps and Ag@siosupporting
confidence: 55%
“…[9] . Previously, the antibacterial action of Ag-based NPs based on dissolved Ag (I) had been reported [9,10,19]. In this work, our results showed that compared to AgNP, Ag (I)-supporting SiO 2 has a significant increase in antibacterial activity.…”
Section: Agnps and Ag@siosupporting
confidence: 55%
“…The study of silver nanoparticles (AgNPs), has undergone a breakthrough in recent decades, mainly due to their optical [1,2] and antimicrobial properties [3][4][5][6]. AgNPs can be prepared by Materials 2020, 13, 503 2 of 17 means of physical, chemical, electrochemical and biological methods [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…They have been attracting interest due to their excellent optical, electrical, thermal, antimicrobial and localised surface plasmon resonance properties [1][2][3]. These nanoparticles (NPs) are already finding applications in a wide variety of fields including printed electronic devices [4], plasmonics [5], antibacterial materials [6] and biosensors [7]. Among these applications, printed electronic devices have gained considerable interest in recent years [8].…”
mentioning
confidence: 99%